Effective Conversion of Heteroaromatic Ketones into Primary Amines via Hydrogenation of Intermediate Ketoximes - Baucom, Kyle D.; Guram, Anil S.; Borths, Christopher J. (Synlett, 2015)
A process to access heteroaromatic primary amines from the corresponding heteroaromatic ketones has been developed. A broad range of previously reported methods to convert ketones to primary amines was examined on heterocyclic ketones without success, including Leuckart–Wallach conditions, borane reductions, and transition-metal-catalyzed hydrogenations. Unique among the catalysts examined, Raney cobalt produced the desired primary heterocyclic amine. Raney cobalt hydrogenation of structurally varied heterocyclic ketoximes was demonstrated to form primary amines in good selectivity under mild conditions, and the products are easily isolated in high yield. Additionally, this is the first report of a systematic evaluation of the capabilities of Raney cobalt as an oxime hydrogenation catalyst.
Keywords: hydrogenation; Raney cobalt; heterogeneous catalysis; amines; reduction; heterocycles